Design, synthesis, biological evaluation and QSAR analysis of novel N-substituted benzimidazole derived carboxamides - Anja Beč; Marija Mioč; Branimir Bertoša; Marija Kos; Patricia Debogović; Marijeta Kralj; Kristina Starčević; Marijana Hranjec (Taylor & Francis Group, 2022)
As a result of our previous research focussed on benzimidazoles, herein we present design, synthesis, QSAR analysis and biological activity of novel N-substituted benzimidazole derived carboxamides. Carboxamides were designed to study the influence of the number of methoxy groups, the type of the substituent placed at the benzimidazole core on biological activity. Pronounced antioxidative activity displayed unsubstituted 28 (IC50 ≈ 3.78 mM, 538.81 mmolFe2+/mmolC) and dimethoxy substituted derivative 34 (IC50 ≈ 5.68 mM, 618.10 mmolFe2+/mmolC). Trimethoxy substituted 43 and unsubstituted compound 40 with isobutyl side chain at N atom showed strong activity against HCT116 (IC50 ≈ 0.6 µM, both) and H 460 cells (IC50 ≈ 2.5 µM; 0.4 µM), being less cytotoxic towards non-tumour cell. Antioxidative activity in cell generally confirmed relatively modest antioxidant capacity obtained in DPPH/FRAP assays of derivatives 34 and 40. The 3D-QSAR models were generated to explore molecular properties that have the highest influence on antioxidative activity.